Antifungal properties in some Malaysian herbal plants - Aziz, Norhalini (2004)
Cassia obtusifolia is a plant that belongs to bean family (Leguminosae). Old folks used to use this plant as a treatment for skin diseases such as ringworm. The common part that is used by the folks is the leaf. Thus, I only use C.obtusifo/ia leaves for my research study. Water extract and ethanol extract of C.obtusifolia leaves is performed in this study. The C.obtusifo/ia leaves were collected at Kampung Sungai Keladi, 2 kilometer from Kota Bharu. The leaves were then washed with tap water before it is rinsed with distilled water. The cleaned leaves were dried in an oven to remove the water contained in the leaves so that the pure component of the plant can be collected. The dried leaves were grinded and ready for extraction process by using sohlex apparatus. Distilled water is used as solvent to form water extract. The extraction process takes approximately 7 days. The residue of the leaves was dried in an oven with temperature of 42°C. After 3 days, when the residue dried, it was mixed with ethanol 95% to form ethanolic extract. Then it was filtered to separate the residue and the extract solution. This is done by using 2 layers of gauze which is placed on top of filter paper in a funnel. These two e~cts were concentrated by means of evaporation. This process is done by using evaporator apparatus. The concentrated water extract was put in universal bottles approximately 1/3 full and it was kept in a freezer before it was lyophilysed. As for ethanol extract, it was put in petri dishes and placed in an oven in order to remove the excess ethanol. Since 95% ethanol was used as solvent, the ethanol extract is naturally oily. The process takes several weeks (approximately 3 weeks). The water extract will be in powder form while ethanol extract will be in oily liquid form. Three concentration of both extract was prepared (1.00 mg/ml, 0.10 mg/ml and 0.01 mglml). Since the folks used to use this plant together with the lime ("kapur''), it is believed that the lime helps in enhancing the effect of the plant. Based on this practice, I tried to add the lime to the water extract and ethanol extract to see their reaction. This mixed-extract was also prepared in three concentrations as water and ethanol extract. The extracts were tested in vitro to fungi. Three types of pathogenic fungi were used for this research namely Cryptococcus neoformans, Candida albican and Candida tropicalis. The test is done by means of agar disc diffusion method. Sabauraud Dextrose Agar (SDA) was used as medium for fungus. Fungal inoculum suspension was prepared from 48 hours old cultures and sterile distilled water. The suspension was adjusted with saline to approximate a density of 1.0 McFarland turbidity standard. The sterile swab was moisten with adjusted inoculum suspension and the surface of the plates was streaked with the swab in two different directions (at 90 degree angles) to cover the entire surface. The tests were done by means of disc diffusion method with three incubation periods (3, 5 and 7 days) and three incubation temperature (28°C, 30°C and 3JOC). The result was red by measuring the zone of inhibition (clear zone) around the test disc. Amphoterism B was used as standard antifungal. TLC was performed at the end of this research.